Avaliação da regeneração natural em pastagem abandonada - Souza, Fernanda Maria de (2015)
The natural regeneration in abandoned pastures undergoes many obstacles, such as the occupation of the area by exotic grasses, soil compaction, limiting seedlings, among others. In this sense, the objective of this study was to evaluate the natural regeneration of a pasture abandoned for 14 years ago. Therefore, we performed the stratification in three size classes of shrub and tree individuals, which are: arboreal (CAP> 15.7cm), juvenile (> = 1.30 m and CAP < 15.7 cm) and regenerating (1-1.3 m of height). The measurement of the arboreal stratum was made using census and juvenile and regenerating strata in nine sample plots (20 x 20 m). The individuals were measured and identified, subsequently obtaining the phytosociological parameters. In each plot, we collected grass biomass, soil samples for chemical and particle size analysis and the corresponding distance to the forest fragment. A total of 55 species was found, including 36 in the arboreal, 30 in the juvenile and 20 in the regenerating strata. There was an expressive importance of pioneer and secondary tree species, among which the Machaerium hirtum is highlighted in the three strata. The dominance of M. hirtum places this species in evidence as a potential species for the restoration of abandoned pastures. The canonical correspondence analysis, regarding the presence and absence of tree species to the environmental variables, showed no significant influence of Brachiaria grass over the composition of tree species of natural regeneration, as well as the distance from the fragment was also not as relevant. On the other hand, we detected a strong influence of elephant grass, very aggressive grass of elevated size, over regeneration. The analyses also showed that species composition is suffering influence of a few soil variables. We can conclude that the canopy formed by M. hirtum individuals may be of great importance for the regeneration at this early stage, however, the indication of control of the elephant grass is necessary due to its expressiveness in the area.